Screening of schiff base ligands derived from phenylenediamine and its metal complexes as a potential efflux pump inhibitor against klebsiella pneumoniae / Norshahida Mat Jaya - Mat Jaya, Norshahida (2020)
A newly synthesized complexes known as Schiff base has become an interesting strategy in the development an alternative treatment against the diseases of multi-drug resistance (MDR) bacteria that are highly resistant to most available antibiotics. Schiff base was produced from a condensation reactions between primary amines and active carbonyl complexes and considered as “privileged ligands” because of their facile preparation and capability to combine and coordinate to other metal and strengthen the combination in different states of condition. These Schiff base metal complexes have attracted interest of many researchers and have been pointed as promising antibiotics and possess so many antibacterial activities. Despite of its versatility, there is still limited research on the screening potential of chemical synthesized of Schiff base ligand and its metal complexes that were derived from phenylenediamine as efflux pump inhibitor in bacterial resistance mechanism. This study focus on the screening of 40 Schiff base complexes that consist of ligands Salicylaldehyde Ortho- phenylenediamine (SalOPD), Ortho-Vanillin Ortho-phenylenediamine (OVanOPD), Ortho-Vanillin Meta-phenylenediamine (OVanMPD), Ortho-Vanillin 2,4,6-trimethyl- m-phenylenediamine [OVan(Me)MPD] and Ortho-Vanillin 4-chloro-1,3- diaminobenzene [OVanMPD(Cl)] and their mono-, di- and tetra- metal of copper, nickel, cobalt and zinc for their antibacterial activity and eventually as efflux pump inhibitor against Klebsiella pneumoniae by resazurin microtiter based assay. The highest antibacterial activity was demonstrated by Cu4[OVan(Me)MPD] that showed 64.2% inhibition against K. pneumoniae. In the other hand, screening for efflux pump inhibitor found that, Co4[OVan(Me)MPD] displayed the highest inhibition percentage of 86.5% when Schiff base complexes and K. pneumoniae ATCC 700603 were treated with the Sub-MIC chloramphenicol (20 μg/mL). Metal complex of copper exhibits highest antibacterial activity among others metal complexes as this due to steadiness of the metal ion which produces a great and strong bond between N and O ions effects from the overlapping of the ligand orbital and partial sharing of positive charge between metal ions of these ligands has decreased the polarity of the ions thus enhances the lipophilicity and improves the cell permeability of the complexes. This situation agree with theory of Overton’s and Tweedy’s theory, where a chemical synthesized of Schiff base metal complexes exhibited better potential as antibiotics as compared to their parent ligands. As a conclusion, unique tetranuclear complexes possess potential for future development of antibacterial agents as well as efflux pump inhibitors.